An infiltration technique for reduction mammaplasty: results in 192 consecutive breasts - O'Donoghue, J. M; Chaubal, N. D; Haywood, R. M; Rickard, R; Desai, S. N (Acta chirurgiae plasticae (English ed.), 1999)
The use of local anaesthetic infiltration with adrenaline is now considered safe in reduction mammaplasty. How- ever, the technique of infiltration by those who support its use is often unclear. Any technique must take account of the neurovascular anatomy of the breast if it is to be effective. We propose the use of a large volume of dilute local anaesthetic (20 ml of 1% lignocaine and 1 mg of adrenaline made up to 400 ml with 0.9% saline) which is placed judiciously in the retroglandular space 15 minutes prior to surgery. The results in 96 consecutive patients (192 breasts) who had an inferior pedicle technique were analysed. The breast complication rate was 9.36 % and the patient complication rate 19.79 %. Postoperative blood loss ranged from 0 to 305 ml with a mean of 56.03 ml and a median of 50 ml. The described method could be considered a variation of the tumescent technique used in liposuction. The re- sults is an almost bloodless dissection with minimal postoperative blood loss. It should be possible to dispense with the use of drains in most cases.
Keywords: dospělí; Mammaplasty; Female; Adult; výsledek terapie; ženské pohlaví; Adolescent; lidé; adrenalin; Treatment Outcome; Lignans; lignany; Epinephrine; lokální anestezie; Anesthesia, Local; lidé středního věku; mamoplastika; Middle Aged; mladiství; Humans